2000
DOI: 10.1046/j.1365-2222.2000.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA genes and susceptibility to toluene diisocyanate‐induced asthma

Abstract: The results of this study indicate that HLA-regulated immune mechanisms are involved in TDI-induced asthma and that, in exposed subjects, specific factors may increase or decrease the risk of developing disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 18 publications
5
61
0
1
Order By: Relevance
“…Although results are still preliminary, several human leukocyte antigen (HLA) markers have been identified that appear to be protective, whereas other markers appear to confer increased risk of WRA (42,43).…”
Section: Work-related Asthma: Workforce-based Studiesmentioning
confidence: 99%
“…Although results are still preliminary, several human leukocyte antigen (HLA) markers have been identified that appear to be protective, whereas other markers appear to confer increased risk of WRA (42,43).…”
Section: Work-related Asthma: Workforce-based Studiesmentioning
confidence: 99%
“…There have been a few HLA association studies in patients with isocyanate-induced asthma. An association of TDI-OA with HLA-DQB1*0503 and an inverse relationship with HLA-DQB1*0501 was found in a European population [17,18,19], whereas no significant HLA association was found in another European study [20]. Recently, we investigated the HLA associations in TDI-OA and found an association between this disease and the DRB1*15-DPB1*05 haplotype in a Korean population, which suggested a susceptible gene marker for TDI-induced asthma [21].…”
Section: Introductionmentioning
confidence: 99%
“…Human lymphocyte antigen (HLA) class 2 molecules have a crucial role in the immune response that occurs in occupational asthma. In one study, 67 workers with TDI induced asthma and 27 asymptomatic controls were genotyped for three HLA class 2 genes: DQA1, DQB1, and DRB1 (Mapp et al, 2000). Asthmatics were found to have a significantly higher frequency of specific alleles for DQA1 and DQB1, while controls had higher frequencies of two other alleles for DQA1 and DQB1.…”
Section: Genetic Polymorphismmentioning
confidence: 99%